A Comprehensive Review Uncovering the Challenges and Advancements in the In Vitro Propagation of Eucalyptus Plantations - Vikas Sharma; Ankita; Arun Karnwal; Shivika Sharma; Barkha Kamal; Vikash S. Jadon; Sanjay Gupta; Iyyakkannu Sivanasen (Plants, 2023)
The genus Eucalyptus is a globally captivated source of hardwood and is well known for its medicinal uses. The hybrid and wild species of Eucalyptus are widely used as exotic plantations due to their renowned potential of adapting to various systems and sites, and rapid large-scale propagation of genetically similar plantlets, which further leads to the extensive propagation of this species. Tissue culture plays a crucial role in the preservation, propagation, and genetic improvement of Eucalyptus species. Despite unquestionable progression in biotechnological and tissue culture approaches, the productivity of plantations is still limited, often due to the low efficiency of clonal propagation from cuttings. The obtained F1 hybrids yield high biomass and high-quality low-cost raw material for large-scale production; however, the development of hybrid, clonal multiplication, proliferation, and post-developmental studies are still major concerns. This riveting review describes the problems concerning the in vitro and clonal propagation of Eucalyptus plantation and recent advances in biotechnological and tissue culture practices for massive and rapid micropropagation of Eucalyptus, and it highlights the Eucalyptus germplasm preservation techniques.